2022
DOI: 10.1021/acs.langmuir.2c00974
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation on the Wettability of Nanoscale Wrinkles: High Water Adhesion of Rose Petals

Abstract: Understanding the high water adhesion of rose petals is of great significance in artificial surface design. With all-atom molecular dynamics simulation, the wettability of nanoscale wrinkles was explored and compared to that of nanoscale strips with favorable hydrophobicity. The dewetting and wetting of gaps between nanoscale structures represent the Cassie–Baxter (CB) and Wenzel (WZ) states of the macroscopic droplet deposited on the textured surface, respectively. We uncovered the intermediate state, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…This same rationale also applies for the negative replicas, which have the same degree of homogenization as that of the positive replicas themselves and thus explains the higher h c for YRN than on RRN. So, in previous studies, the influence of the complex hierarchical structures that are omnipresent on these biological surfaces over the static wetting states have been studied, 13,14,32 but the dynamic wetting states over such short times have been missing. This is shown here for the first time that over a much shorter time such as during droplet impact, the same hierarchical structures that show sticky superhydrophobicity reveal a myriad of other wetting states including the completely opposite superhydrophobicity as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This same rationale also applies for the negative replicas, which have the same degree of homogenization as that of the positive replicas themselves and thus explains the higher h c for YRN than on RRN. So, in previous studies, the influence of the complex hierarchical structures that are omnipresent on these biological surfaces over the static wetting states have been studied, 13,14,32 but the dynamic wetting states over such short times have been missing. This is shown here for the first time that over a much shorter time such as during droplet impact, the same hierarchical structures that show sticky superhydrophobicity reveal a myriad of other wetting states including the completely opposite superhydrophobicity as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A more recent study revealed that this petal effect may also find its origin in the chemical heterogeneity at the nanoscale . Another molecular dynamics simulation study showed that the higher wettability of the nanowrinkles is the reason for such high adhesion . However, it is envisaged that such a surface can be employed to hold a drop of liquid against gravity and to suppress any spill to the neighboring areas after depositing a droplet, ,,,, including possible fabrication of stable slippery surfaces by anchoring the slip enhancing the oil layer against the gravity-mediated drainage and also for maneuvering droplets over them .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the experimental studies demonstrate that the hydrophobicity of EP surfaces presents nonlinearities as a function of polar composition, where the increased hydrophilic polar groups do not boost the hydrophilicity on the solid surface. Molecular dynamics calculation has been proven an effective method as a supplement to study the surface wetting properties. Here, to reveal the underlying mechanism on the wetting property, the interaction between water and EP molecules before and after ozone treatment is studied by molecular simulation using Material Studio.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that the mechanical properties of biological tissues are complex, especially the weak adhesion force on the surface of tissues, which is difficult to measure. In the following work, we will continue to further miniaturization design, and consider adding nanoscale structures 36 or charge modification 37 on the surface of optical waveguide to achieve higher adhesion sensitivity. We anticipate that the system can assist with minimally invasive surgery and provide adhesion information on the surface of organs in the future.…”
Section: ■ Conclusionmentioning
confidence: 99%